Ayurvedic Perspective of Abnormal Vaginal Discharge (AYUSHDHARA, 2024)
In the context of wide prevalence and growing incidence of abnormal vaginal discharge throughout the globe and due to the lack of effective and safe therapy in modern science, there is an increasing focus on alternative systems of medicine. Ayurveda is an age-old life science that offers great potential in treating the symptom. The present study was taken up to review the theoretical foundations and empirical evidence of Ayurvedic drugs for this.Apart from consulting the texts in Ayurveda and modern systems, the study got access to internet sources like AYUSH Portal and PubMed, Google Scholar etc. Out of 90 papers identified, forty research papers were selected for review on various aspects of AVD, such as observational studies, clinical studies, review studies. They are reviewed for theoretical background, research techniques adopted, the drugs and methods employed for treatment and the parameters chosen for evaluation of the effects of these drugs.The results show that Ayurveda has both theoretical foundations and empirical evidence of efficacy of Ayurvedic drugs and shows the promise of evolving a polyherbal formulation to address the symptom holistically.